Serum ferritin level and its association with gestational diabetes mellitus in pregnancy - N., Anushree; Prabhu, Sujatha; Fathima, Sana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Short term as well as long term effects of GDM on both the mother and the child are preventable if screening and diagnosis are done at an early stage. Efforts have been made to try and identify clinical and biochemical markers that could predict GDM. Ferritin, an acute phase reactant is one such protein. This study was undertaken to know if there is an association between serum ferritin level and GDM in pregnancy. Methods: A prospective study conducted in the Department of OBG, ESIC-MC-PGIMSR from January 2020 to June 2021. 388 gravid women satisfying the inclusion criteria were enrolled for the study after obtaining an informed written consent and maternal serum ferritin was assayed between 24 to 28 weeks of gestation and was statistically analysed. Results: Both group demographic characters were matched and they were also matched for Hb% thereby eliminating anaemia, a confounding factor for the study. The mean serum ferritin level in GDM group was 46.4 ng/ml and in non-GDM group was 37.3 ng/ml (p<0.001). With ROC (Receiver operator characteristics curve) the cut off value of serum ferritin is 34.7 ng/ml with 95% CI, with sensitivity of 71% and specificity of 63%. Conclusions: In this study S. ferritin value of >34.7 ng/ml at 24-28 weeks of gestation, there is 63% risk of developing GDM. Thus, we conclude that elevated serum ferritin level could be used as a biochemical marker for prediction of GDM.